An Experimental Study on Axial Stress-Strain Behaviour of FRP-Confined Square Lightweight Aggregate Concrete Columns - Butje Alfonsius Louk Fanggi; Budi Suswanto; Yuyun Tajunnisa; Jusuf Wilson Meynerd Rafael; Jonatan Lassa; Ahmad Basshofi Habieb (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
This article presents the results of a research project that aimed to evaluate how the number of fiber-reinforced polymer (FRP) layers and the compressive strength of concrete affect the stress-strain behaviors of concrete columns produced from artificial lightweight aggregate with square cross-sectional shapes. Eighteen test specimens were manufactured and wrapped with glass fiber-reinforced polymer (GFRP) material. The specimens were later subjected to concentric compression for experimental evaluation. The experimental results suggest that GFRP efficiently confines square lightweight aggregate concrete columns. Furthermore, the test results indicate that adding FRP layers augments the ultimate stress and strain. Finally, the results suggest that an increase in the compressive strength of concrete leads to a corresponding increase in the ultimate stress. On the other hand, it has been observed that the ultimate strain decreases as compressive strength increases. The research findings reveal the behaviour of FRP-confined square lightweight aggregate concrete columns, which may also be utilized to formulate a new design-oriented model for these columns.